The contemporary world - Lobo, Joliver L.; Ambida, Melvin N.; Maliban, Niño P.; Mesinas, Michael M. (Mandaluyong City: Books Atbp. Publishing Corp., 2019)
"This book provides a broad background and introduction to key people, events, and larger social, economic, technological, political, cross-cultural and global forces that have shaped our current world and created many of the problems of today."
Includes references.
English text.
Keywords: Globalization